2012
DOI: 10.1002/clc.21986
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics, Sex Hormones, and Long‐Term Follow‐Up in Swiss Postmenopausal Women Presenting With Takotsubo Cardiomyopathy

Abstract: Background:The overwhelming majority of patients with stress cardiomyopathy (SC) are postmenopausal women, suggesting an important pathophysiologic role of the female sex hormones. Preliminary data suggest that myocardial stunning might be provoked by estrogen deficiency. Hypothesis: We hypothesized that, compared with age-and gender-matched patients with myocardial infarction (MI) or patients with normal coronary arteries, patients with SC would exhibit altered levels of sex hormones. Furthermore, we aimed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 54 publications
2
28
0
3
Order By: Relevance
“…This may be of importance since spontaneous coronary dissection (and perhaps other unusual mechanisms of MI), may occur during times of widely fluctuation estrogen levels. 12,13 Similar to this current report, prior studies have shown that high thrombus burden, low initial flow, larger baseline infarct size, low ejection fraction, anterior MI, prior MI, C-reactive protein, elevated blood counts, high SYNTAX score, and delay in reperfusion were predictive of no-reflow after primary PCI. [14][15][16] The potential mechanism of no-reflow is multifactorial, and may include platelet and leukocyte plugging, distal embolization, myocardial edema, and/ or reperfusion injury.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…This may be of importance since spontaneous coronary dissection (and perhaps other unusual mechanisms of MI), may occur during times of widely fluctuation estrogen levels. 12,13 Similar to this current report, prior studies have shown that high thrombus burden, low initial flow, larger baseline infarct size, low ejection fraction, anterior MI, prior MI, C-reactive protein, elevated blood counts, high SYNTAX score, and delay in reperfusion were predictive of no-reflow after primary PCI. [14][15][16] The potential mechanism of no-reflow is multifactorial, and may include platelet and leukocyte plugging, distal embolization, myocardial edema, and/ or reperfusion injury.…”
supporting
confidence: 84%
“…Whereas estrone is primarily generated by adipose tissue, the estradiol may be generated from adipose or from residual ovarian function. This may be of importance since spontaneous coronary dissection (and perhaps other unusual mechanisms of MI), may occur during times of widely fluctuation estrogen levels …”
mentioning
confidence: 99%
“…Seven studies on the effects of β‐blockers on the prevention of TTC recurrence were evaluated in a pooled analysis . In aggregate, the pooled studies included 471 subjects.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining 165 records were screened, and 140 of them were excluded because the median follow‐up was shorter than 3 months. Twenty‐five full‐text articles were assessed for eligibility, but only 8 studies met all the inclusion criteria (Table ) …”
Section: Methodsmentioning
confidence: 99%
“…Estrogen deficiency in the postmenopausal state may play a role [47] . Of particular interest, in other conditions with elevated catecholamine levels like subarachnoid hemorrhage, segmental wall motion abnormality is also predominantly seen in women.…”
Section: Stress-induced or "Takotsubo" Cardiomyopathymentioning
confidence: 99%